2018
DOI: 10.1111/pbi.13014
|View full text |Cite
|
Sign up to set email alerts
|

Molecular tools enabling pennycress (Thlaspi arvense) as a model plant and oilseed cash cover crop

Abstract: Thlapsi arvense L. (pennycress) is being developed as a profitable oilseed cover crop for the winter fallow period throughout the temperate regions of the world, controlling soil erosion and nutrients run-off on otherwise barren farmland. We demonstrate that pennycress can serve as a user-friendly model system akin to Arabidopsis that is well-suited for both laboratory and field experimentation. We sequenced the diploid genome of the spring-type Spring 32-10 inbred line (1C DNA content of 539 Mb; 2n = 14), ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 71 publications
0
77
0
1
Order By: Relevance
“…In theory, it would have been faster to use gene-editing approaches to create the domestication traits described in this report. In fact, we have created an alternative zero erucic acid pennycress line using CRISPR-Cas9 mediated gene editing (McGinn et al 2018). However, successful utilization of gene editing requires precise knowledge about the genes one wishes to target.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, it would have been faster to use gene-editing approaches to create the domestication traits described in this report. In fact, we have created an alternative zero erucic acid pennycress line using CRISPR-Cas9 mediated gene editing (McGinn et al 2018). However, successful utilization of gene editing requires precise knowledge about the genes one wishes to target.…”
Section: Discussionmentioning
confidence: 99%
“…Such edits were detectable in sequence traces from T 1 GE plants, and trace analysis was therefore recommended. Michaela had used CRISPR‐Cas9 to reduce the levels of an undesired fatty acid from 40% in WT Pennycress seed to < 1% in GE mutants (McGinn et al ., ).…”
Section: Technical Considerations Relating To Gementioning
confidence: 97%
“…A recent evaluation of genetic diversity showed that the genetic variation present in North American pennycress accessions was limited (Frels et al 2017). Therefore, alternative tools such as chemical mutagenesis and gene editing have been used to create genetic variation for key domestication traits (Chopra et al , 2019aMcGinn et al 2018).…”
Section: Germplasm Developmentmentioning
confidence: 99%
“…The reduction in erucic acid and sinigrin content has largely followed the steps laid out by researchers who developed canola from rapeseed (Bell 1982;Claver et al 2017). Recently, pennycress lines with reduced erucic acid content and increased oleic, linoleic, and linolenic acid content were identified through the use of both chemical mutagenesis and CRISPR-Cas9 gene editing (McGinn et al 2018;Chopra et al 2019b). In addition, pennycress lines with reduced sinigrin and silicle shatter were identified (Chopra et al 2019b).…”
Section: Germplasm Developmentmentioning
confidence: 99%